Development of a new multimedia instrument to measure cancer-specific quality of life in Portuguese-speaking patients with varying literacy skills - Paiva, Carlos Eduardo; Siquelli, Felipe Augusto Ferreira; Zaia, Gabriela Rossi; de Andrade, Diocésio Alves Pinto; Borges, Marcos Aristoteles; Jácome, Alexandre A.; Giroldo, Gisele Augusta Sousa Nascimento; Santos, Henrique Amorim; Hahn, Elizabeth A.; Uemura, Gilberto [UNESP]; Paiva, Bianca Sakamoto Ribeiro (Springer Nature, 2016)
Purpose: To develop and validate a new multimedia instrument to measure health-related quality of life (HRQOL) in Portuguese-speaking patients with cancer. Methods: A mixed-methods study conducted in a large Brazilian Cancer Hospital. The instrument was developed along the following sequential phases: identification of HRQOL issues through qualitative content analysis of individual interviews, evaluation of the most important items according to the patients, review of the literature, evaluation by an expert committee, and pretesting. In sequence, an exploratory factor analysis was conducted (pilot testing, n = 149) to reduce the number of items and to define domains and scores. The psychometric properties of the IQualiV-OG-21 were measured in a large multicentre Brazilian study (n = 323). A software containing multimedia resources were developed to facilitate self-administration of IQualiV-OG-21; its feasibility and patients’ preferences (“paper and pencil” vs. software) were further tested (n = 54). Results: An exploratory factor analysis reduced the 30-item instrument to 21 items. The IQualiV-OG-21 was divided into 6 domains: emotional, physical, existential, interpersonal relationships, functional and financial. The multicentre study confirmed that it was valid and reliable. The electronic multimedia instrument was easy to complete and acceptable to patients. Regarding preferences, 61.1 % of them preferred the electronic format in comparison with the paper and pencil format. Conclusions: The IQualiV-OG-21 is a new valid and reliable multimedia HRQOL instrument that is well-understood, even by patients with low literacy skills, and can be answered quickly. It is a useful new tool that can be translated and tested in other cultures and languages.
Keywords: Development; IqualiV-OG-21; Low literacy; Multimedia; Quality of life; Validation